THE RELATIONSHIP OF TAX LITERACY, TAX KNOWLEDGE, AND TAX SOCIALIZATION IN CULTIVATING TAX AWARENESS AMONG HIGHER EDUCATION STUDENTS IN MALAYSIA - Veeraselvam, Satiaseela; Ismail, Zuriadah; Halim, Hazianti Abdul (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2025)
Maintaining Malaysia’s national income and promoting public development depend heavily on tax compliance. Students in higher education are a significant future taxpayer demographic, and their long-term compliance behaviour is critically influenced by their tax awareness. This study determine using survey on how tax awareness among university students is influenced by tax literacy, tax knowledge, and tax socialization. This study incorporates the cognitive, attitudinal, and social aspects of behaviour by drawing on three theories such as Experiential Learning Theory (ELT), the Theory of Planned Behaviour (TPB), and Social Learning Theory (SLT). The findings are anticipated will help educators, curriculum designers and policymaker to create focused interventions to increase voluntary tax compliance at the young ages.